2021
DOI: 10.1093/mnras/stab2734
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of neutron star natal kicks using proper motions and parallax measurements for radio pulsars and Be X-ray binaries

Abstract: Supernova explosion and the associated neutron star natal kicks are important events on a pathway of a binary to become a gravitational wave source, an X-ray binary or a millisecond radio pulsar. Weak natal kicks often lead to binary survival, while strong kicks frequently disrupt the binary. In this article, we aim to further constrain neutron star natal kicks in binaries. We explore binary population synthesis models by varying prescription for natal kick, remnant mass and mass accretion efficiency. We intro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 104 publications
5
23
1
Order By: Relevance
“…Of the remaining 20, two have apparently stellar properties broadly consistent with expectations for bound companions (CXOU J1714 and SGR 0755, for which the bright star is a confirmed HMXB, but may but a chance alignment with the magnetar in question). consistent with the upper end of compact remnant-massive star bound systems, specifically high-mass X-ray binaries (Mirabel et al 2002;Atri et al 2019;Igoshev et al 2021). If we instead adopt a distance of 5 kpc -the lowest distance estimated for CXOU J1714 before it was revised upwards by association with the CTB 37 supernova remnant complex (Tian & Leahy 2012) -the transverse velocity estimate drops to 140 ± 67 kms −1 , entirely consistent with bound systems.…”
Section: Cxouj1714supporting
confidence: 56%
See 1 more Smart Citation
“…Of the remaining 20, two have apparently stellar properties broadly consistent with expectations for bound companions (CXOU J1714 and SGR 0755, for which the bright star is a confirmed HMXB, but may but a chance alignment with the magnetar in question). consistent with the upper end of compact remnant-massive star bound systems, specifically high-mass X-ray binaries (Mirabel et al 2002;Atri et al 2019;Igoshev et al 2021). If we instead adopt a distance of 5 kpc -the lowest distance estimated for CXOU J1714 before it was revised upwards by association with the CTB 37 supernova remnant complex (Tian & Leahy 2012) -the transverse velocity estimate drops to 140 ± 67 kms −1 , entirely consistent with bound systems.…”
Section: Cxouj1714supporting
confidence: 56%
“…We also investigate the impact of assuming different neutron star natal kick velocities -the kick distributions of Hobbs et al (2005) and Igoshev (2020) yield very similar f bound values of 0.049 and 0.050. Igoshev et al (2021) also found little difference between these kicks in terms of the Be star mass distribution in X-ray binaries. The kick of Bray & Eldridge (2016, however, gives a substantially larger value of 0.23.…”
Section: Uncertaintiesmentioning
confidence: 83%
“…Besides the stellar collapse and SN engine mechanism which is the main subject of this work, there are many other uncertain processes that dictate the formation of DCO mergers. Some examples of such processes or parameters which may significantly influence physical properties of DCO mergers are: the metallicity-specific star formation rate density and initial mass function (Chruślińska et al 2020;Santoliquido et al 2021;Broekgaarden et al 2021a;Briel et al 2021;Kroupa & Jerabkova 2021), stellar winds (Vink et al 2001;Sander et al 2022), convection and overshooting (Klencki et al 2021;Belczynski et al 2022), NS and BH natal kicks (Mandel et al 2021;Igoshev et al 2021), type and rate of mass transfer and the outcome of stable/unstable RLOF (Vinciguerra et al 2020;Howitt et al 2020;Bavera et al 2020;Vigna-Gómez et al 2022). The assumptions adopted for this work are described in Section 2.…”
Section: Discussion Of Caveats and Uncertaintiesmentioning
confidence: 99%
“…We also investigate the impact of assuming different neutron star natal kick velocities -the kick distributions of Hobbs et al ( 2005 ) and Igoshev ( 2020 ) yield very similar f bound values of 0.049 and 0.050. Igoshev et al ( 2021 ) also found little difference between these kicks in terms of the Be star mass distribution in X-ray binaries. The kick of Bray & Eldridge ( 2016 ) and Bray & Eldridge ( 2018 ), ho we ver, gi ves a substantially larger value of 0.23.…”
Section: Uncertaintiesmentioning
confidence: 83%